Imperfection in the Capital Market and the Institutional Arrangement of Inheritance - Ishikawa, Tsuneo (Review of Economic Studies, 1974)
Journal Article Imperfection in the Capital Market and the Institutional Arrangement of Inheritance Get access Tsuneo Ishikawa Tsuneo Ishikawa Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 3, July 1974, Pages 383–404, https://doi.org/10.2307/2296757 Published: 01 July 1974